Menière's Disease and Disorders of the Carbohydrate Metabolism Involving the Inner Ear - Albernaz, Pedro L. Mangabeira (International Archives of Otorhinolaryngology, 2019)
Introduction Menière’s disease was described in 1861, but there are still uncertainties regarding its pathophysiology and treatment. Endolymphatic hydrops is recognized as a fundamental pathological characteristic of the disease, as a result of an inadequate absorption of the endolymph. A milder type of endolymphatic hydrops results from an altered chemical composition of the endolymph, due to disorders of the carbohydrate metabolism.Objective To describe the association of both types of hydrops in patients with Menière disease.Methods This was a retrospective study of 98 patients with Menière’s disease, 62 of whom also presented disorders of the carbohydrate metabolism, and 5 patients with delayed endolymphatic hydrops, 2 of whom also presented disorders of the carbohydrate metabolism.Results The follow-up of these patients showed that the correction of the metabolic disorders may help in the clinical treatment of Menière’s disease and of delayed endolymphatic hydrops, but this does not happen in the more severe types of the diseases.Conclusion Patients with Menière’s disease may present simultaneous disorders of the carbohydrate metabolism, affecting the inner ear. The correction of these disorders helps the clinical treatment but does not preclude the progression of the more severe cases of Menière disease.
Keywords: menière’s disease; carbohydrate metabolism; endolymphatic hydrops